Antimicrobial investigation on Morinda tomentosa Heyne ex Roth. - K.V. Kothale3, S.P. Rothe1*, A.S. Pethe2 (Journal of Ecobiotechnology, 2011)
Ayurveda is the traditional system of medicine widely practiced in India and was popular before the advent of modern medicine. Modern medical science considered that microbes are believed to be primary causative agents of various diseases. Medicinal plants have been an important source of drug for treatment of diseases. The species of Morinda tomentosa was collected from Akola district of Vidarbha region. Plant extract like leaves and fruit extract was studied for its antimicrobial activity against human pathogens. In present investigation six clinical isolates bacteria were studied for their susceptibility to leaf and fruit extract. Among six pathogens Staphylococcus aureus and K. pnemoniae were highly sensitive to M. tomentosa leaf and fruit extract.